A Cell Membrane Targeting Molybdenum-Iodine Nanocluster: Rational Ligand Design toward Enhanced Photodynamic Activity - Kirakci, Kaplan; Kubáňová, Michaela; Přibyl, Tomáš; Rumlová, Michaela; Zelenka, Jaroslav; Ruml, Tomáš; Lang, Kamil (Inorganic chemistry, 2022)
The development of singlet oxygen photosensitizers, which target specific cellular organelles, constitutes a pertinent endeavor to optimize the efficiency of photodynamic therapy. Targeting of the cell membrane eliminates the need for endocytosis of drugs that can lead to toxicity, intracellular degradation, or drug resistance. In this context, we utilized copper-free click chemistry to prepare a singlet oxygen photosensitizing complex, made of a molybdenum-iodine nanocluster stabilized by triazolate apical ligands. In phosphate-buffered saline, the complex formed nanoaggregates with a positive surface charge due to the protonatable amine function of the apical ligands. These nanoaggregates targeted cell membranes and caused an eminent blue-light phototoxic effect against HeLa cells at nanomolar concentrations, inducing apoptotic cell death, while having no dark toxicity at physiologically relevant concentrations. The properties of this complex were compared to those of a negatively charged parent complex to highlight the dominant effect of the nature of apical ligands on biological properties of the nanocluster. These two complexes also exerted (photo)antibacterial effects on several pathogenic strains in the form of planktonic cultures and biofilms. Overall, we demonstrated that the rational design of apical ligands toward cell membrane targeting leads to enhanced photodynamic efficiency.
Keywords: buněčná membrána; Ligands; jod; molybden; Cell Membrane; Humans; HeLa buňky; ligandy; lidé; HeLa Cells; Iodine; Molybdenum